Role of Podoplanin-Positive Cells in Cardiac Fibrosis and Angiogenesis After Ischemia - Cimini, Maria; Kishore, Raj (Frontiers in Physiology, 2021)
New insights into the cellular and extra-cellular composition of scar tissue after myocardial infarction (MI) have been identified. Recently, a heterogeneous podoplanin -expressing cell populations has been associated with the fibrogenic and inflammatory responses and lymphatic vessel growth during the scar formation. Podoplanin is a mucin-like transmembrane glycoprotein that plays an important role in heart development, cell motility, tumorigenesis and metastasis. In the adult mouse heart, podoplanin is expressed only by cardiac lymphatic endothelial cells; after MI, it is acquired with an unexpected heterogeneity by PDGFRα, PDGFRβ and CD34 positive cells. Podoplanin therefore may represent a sign of activation of a cohort of progenitor cells during different phases of post-ischemic myocardial wound repair. Podoplanin binds to C-type lectin-like receptor 2 (CLEC-2) which is exclusively expressed by platelets and a variety of immune cells. CLEC-2 is upregulated in CD11bhigh cells including monocytes and macrophages following inflammatory stimuli. We recently published that inhibition of the interaction between podoplanin-expressing cells and podoplanin-binding cells using podoplanin-neutralizing antibodies reduces but does not fully suppress inflammation post MI while improving heart function and scar composition after ischemic injury. These data support an emerging and alternative mechanism of interactome in the heart that, when neutralized, leads to altered inflammatory response and preservation of cardiac function and structure. The overarching objective of this review is to assimilate and discuss available evidence on the functional role of podoplanin positive cells on cardiac fibrosis and remodeling. A detailed characterization of cell-to-cell interactions and paracrine signals between podoplanin expressing cells and the other type of cells that compose the heart tissue is needed to open a new line of investigation extending beyond known function of these cells. This review attempts to discuss the role and biology of podoplanin positive cells in the context of cardiac injury, repair, and remodeling.